Optimization of Education Quality Improvement in Early Childhood Education (PAUD) in Sukmajaya District, Depok City through the Role of School Leadership and Teacher Performance - Radhiyya Aisya Arimbi Alvianti; Ali Ridho; Udriyah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Human Resources (HR) are a dominant factor in every institution, including in the field of education. Education requires excellent HR to fulfill its role in meeting the educational needs of society. Therefore, to generally improve the quality of human resources effectively, learning in schools is essential. The role of school leadership must have the ability to optimize all available resources in the school to realize the vision and mission established to achieve the predetermined goals. In addition to the role of school leadership, teacher performance also plays a crucial role in improving the quality of education. The number of competent early childhood education (PAUD) educators is still insufficient, and many principals and teachers have not yet undergone training. This issue needs to be addressed promptly, considering the important role of educators in the education system in Indonesia. This research uses a quantitative approach. It aims to measure the significant influence of the role of school leadership and teacher performance on the quality of education in PAUD throughout the Sukmajaya District of Depok City. The results of hypothesis testing and multiple linear regression show that the role of school leadership and teacher performance have a positive and significant impact on the quality of education in PAUD throughout the Sukmajaya District of Depok City. The adjusted R-squared value (Adj R2) is 0.961, indicating that the contribution of the independent variables, namely the role of school leadership and teacher performance, to the dependent variable, which is the quality of education, is 96.1%, while the remaining 3.9% is influenced by other variables not examined or included in this regression study.